Clinical Case and Follow‐Up of Babesia banethi Infection in a Red Fox - Mariaelisa Carbonara; Michela Prioletti; Antonio Camarda; Stefano Castellana; Giuseppe Menga; Giovanna Girardi; Gad Baneth; Domenico Otranto (Veterinary Medicine and Science, 2026)
ABSTRACT Background Red foxes play an important role in the circulation of ticks and tick‐borne pathogens, including Babesia spp. While for Babesia vulpes many studies are available on its epidemiology in fox populations as well as pathogenicity in dogs, no data are reported for the recently described Babesia banethi infecting red foxes. Objective Here we describe the clinical and parasitological follow‐up of a naturally occurring B. banethi infection in a red fox from southern Italy. Case presentation An adult male fox presented with severe debilitation, weight loss, pale mucous membranes, brown discolouration of urine and sarcoptic mange. Haematological examination revealed regenerative anaemia associated with left‐shift neutrophilia and lymphocytosis. Blood smear examination showed intraerythrocytic inclusions morphologically consistent with small piroplasmids, and PCR amplification and sequencing of the 18S rDNA gene confirmed infection with B. banethi . Screening for other vector‐borne pathogens scored negative. Treatment with imidocarb dipropionate resulted in temporary clinical and haematological improvement but persistence of PCR positivity and later relapse of parasitaemia and clinical signs. Subsequently, treatment with atovaquone/proguanil combined with azithromycin led to marked clinical recovery and disappearance of parasites at blood smear examination, although PCR positivity persisted for several months. A second therapeutic course resulted in both cytological and molecular negativity. Conclusions This longitudinal case report provides the first detailed account of the clinical course, therapeutic response and long‐term parasitological follow‐up of B. banethi infection in a red fox, suggesting that this piroplasm might cause clinically relevant and persistent infection, yet further validation of this hypothesis on a larger number of clinical cases is advocated. Clinical study registration Not applicable.